Simulação computacional da prensagem de pós para a previsão de falhas em compactos verdes - Furlan, Matheus (2024)
Numerical simulation is a powerful tool for reducing production costs and improving dimensional tolerance and mechanical properties of parts produced by powder pressing. The prediction of mechanical properties in green compacts, during and after compaction, is crucial for ensuring part integrity in subsequent processes, such as green machining and sintering. However, failure prediction in green compacts is a field yet to be explored. Additionally, the constitutive models used to represent the mechanical behavior of the powder calls for various calibration procedures. In this context, this project aims to explore the use of experimental procedures and numerical simulations to predict failures in green compacts. To do so, closed-die pressing tests were conducted using an instrumented die equipped with strain gauges, pistons with axial sensors, an axial load cell, and an LVDT sensor. The experimental signals were compared with their numerical counterparts to adjust the parameters of the Drucker-Prager/Cap (DPC) constitutive model, based on parameters obtained from the literature. Two materials were evaluated: alumina powder and PTFE powder. After these adjustments, rubber multiaxial pressing (RMP) tests were planned via numerical simulations, aiming at a geometry/condition in which pinching of the elastomeric mold occurs on the green compact. Experimentally, fractures were observed for both materials. By post-processing the simulation results of these RMP tests, it was possible to validate the DPC model as an indicator of the failures observed experimentally, despite the model's development for simulating material consolidation. The agreement was higher for greater pressure and density levels, and for alumina powder. Thus, the use of DPC models during pressing simulations may provide valuable information about certain conditions and regions that might experience failure, which can be directly applied to rubber mold projects for isostatic pressing and rubber multiaxial pressing.